2019
DOI: 10.33182/bc.v9i2.823
|View full text |Cite
|
Sign up to set email alerts
|

A Multireligious Approach to the Integration of Migrants in Europe: An Examination of Migrants’ Views on and Experiences of Taking Part in Multireligious Integration Projects

Abstract: Violent conflicts continue to force many migrants to seek protection outside their own country. Some of these migrants have come to Europe, leading to states relying on assistance from civil society organisations, some of which are Faith-based Organisations (FBOs), to meet the migrants’ complex needs. Whereas the important roles religious actors can play in integration processes have been increasingly addressed and acknowledged in the literature, multireligious cooperation on integration has yet to attract the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Using group activities, such as sports, and festivals, Goda Grannar linked migrants to other people and networks that migrants could tap into in the future. These findings bode well for other Christian and Muslim integration projects in other cities in Sweden, as well as similar projects in Germany and the UK since research has already shown that taking part in multireligious projects in these countries has helped migrants to integrate (Lyck-Bowen 2019). Future research should evaluate how multireligious cooperation in other settings and countries influences migrant and refugee integration.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Using group activities, such as sports, and festivals, Goda Grannar linked migrants to other people and networks that migrants could tap into in the future. These findings bode well for other Christian and Muslim integration projects in other cities in Sweden, as well as similar projects in Germany and the UK since research has already shown that taking part in multireligious projects in these countries has helped migrants to integrate (Lyck-Bowen 2019). Future research should evaluate how multireligious cooperation in other settings and countries influences migrant and refugee integration.…”
Section: Discussionsupporting
confidence: 74%
“…In many countries, faith-based organizations (FBOs) are now actively involved in helping to welcome and integrate migrants (CCME 2015; Hough 2016; Lyck-Bowen and Owen 2018; Lyck-Bowen 2019). This is not new; many Christian FBOs have a long-standing tradition of aiding migrants in need, working alone or with secular partners to welcome and integrate migrants (Lyck-Bowen and Owen 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…143 Drawing on her pilot study, Lyck-Bowen suggests that multi-faith cooperation might allow scholars to tackle it. 144 There is evidence that multi-faith initiatives allow people on the move to better understand the role that religion plays in their new country. 145 Dichotomies between insiders and outsiders that are rooted in religion-as in the clash of civilisations-are destabilised.…”
Section: Countering Ethical Frames: Multi-faith Practice As a Point O...mentioning
confidence: 99%
“…Migration is a meaningful and sometimes traumatic experience. Religious faith and participation provide cultural continuity and bridges between the old world and the new by offering metaphysical guidance in the spatial journey and enhancing immigrants' consciousness of their religious roots (Kagan, Fong and Reitz, 2020;Lyak-Bowen, 2019;Rebhun, 2014;Vilaca et al, 2014). An immigrant's religious community replaces her or his extended family as a source of social comfort, a framework for ethnic celebration, and a place to seek assistance in realizing economic opportunities (Cadge and Ecklund, 2007).…”
Section: Religiositymentioning
confidence: 99%